Novel floxed cannabinoid receptor 2 mouse line combines knockout capability with dual fluorescent reporters - Laloli, Kathryn J.; Rentsch, Peggy; Stayte, Sandy; Vissel, Bryce (Frontiers in Pharmacology, 2025)
BackgroundThe cannabinoid receptor 2 (CB2) is involved in regulating immune responses, yet its specific function in microglia remains poorly defined. This study aimed to generate and validate a microglia-specific, inducible CB2 knockout mouse model incorporating reporter genes to enable precise detection of CB2 expression and CB2 knockout.MethodsA novel floxed CB2 mouse line was generated, incorporating GFP and tdTomato reporter genes driven by the Cnr2 promoter to indicate CB2 expression and CB2 knockout, respectively. This line was crossed with Cx3cr1 or Tmem119 tamoxifen-inducible Cre lines to achieve macrophage- or microglia-specific CB2 knockout, respectively. Behavioural testing, in vitro assays, sequencing and in vivo immunofluorescence were used to assess the efficiency and specificity of CB2 knockout as well as potential off-target effects.ResultsThe floxed allele did not alter breeding or motor behaviour in mice, nor CB2 function. CB2 expression, indicated by GFP, followed expected patterns across tissues and conditions. Sequencing revealed both DNA and RNA of the floxed allele was as anticipated. Tamoxifen-induced Cre activity successfully initiated tdTomato expression exclusively in microglia of tamoxifen treated, Cre positive mice, validating the specificity and inducibility of CB2 knockout. Microglial tdTomato expression confirmed successful CB2 knockout in 9.3% of TmemCB2 and 91.7% of Cx3CB2 microglia. Peripheral tdTomato expression persisted beyond 3 weeks post-tamoxifen in Cx3CB2 mice but was minimal in TmemCB2 mice.ConclusionThis novel microglia-specific, inducible CB2 knockout model is the first to combine a floxed CB2 allele with reporter genes, an essential advancement given the lack of reliable CB2 antibodies. The findings demonstrate the model’s specificity and effectiveness, while highlighting important considerations regarding Cre-mediated effects and recombination specificity. Furthermore, the floxed mouse can be crossed with any Cre line to study CB2 expression and function in various tissues. This model provides a powerful platform for advancing understanding of CB2 roles in microglia and supports future exploration of CB2-targeted therapeutic strategies.